THE INFLUENCE OF LEARNING METHODS AND NATURALIST INTELLIGENCE ON CRITICAL THINKING SKILLS IN SCIENCE LEARNING - Suhirman Suhirman (Jurnal Tatsqif, 2020)
The purpose of this research is to find out the influence of different learning methods and nauralist intelligence on critical thinking skills on science learning. This research method uses an experimental approach. The data in this resarch was collected with observation techniques for the implementation of learning and tests to measure naturalist intelligence and critical thinking skills. To determine the influence of different learning methods and nauralist intelligence on critical thinking skills on science learning, analysis was conducted with t-Test Two-Sample Assuming Equal Variances. There is an influence on students’ nauralist intelligence level on critical thinking skills taught by problem-based learning methods as evidenced by the results of the analysis where tcount = 6.89 > ttable= 2.03, thus positively correlated with a determination coefficient of 0.58. On the other hand, there is no influence on students’ level of nauralist intelligence on critical thinking skills taught by regular learning methods, which is evidenced by the results of the analysis where tcount = 0.06= ttable= 2.03, so it does not correlate positively with the coefficient of determination of 0.0001. From various literature stipulated that problem based learning is a teaching approach that uses real-world problems as a context for students to learn about critical thinking and problem solving skills, as well as to obtain essential knowledge and concepts from the subject matter.